2021
DOI: 10.1016/j.jcot.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategies for prevention of amputation of the diabetic foot

Abstract: Prevention of amputation has become a key objective of clinicians providing care to patients with highrisk diabetic foot problems. In this regard, the multidisciplinary diabetic foot team (MDFT) has been embraced as the most effective way to manage patients with foot ulcers, infections, and Charcot feet. Importantly, such specialized teams have also integrated various surgical specialties to enable more expedient management of these often complex conditions. Experienced diabetic foot surgeons over the last thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…While our data did not categorize specific levels of amputations performed, modern limb-salvage practice has a relatively low threshold for such minor amputations in the presence of deteriorating diabetic foot wounds. 28 This is reflected in recent nation-wide increases in the rate of diabetes-related minor amputations in the United States, manifested as a 50% increase in the total amputation rate in the years 2009–2015. 29…”
Section: Discussionmentioning
confidence: 99%
“…While our data did not categorize specific levels of amputations performed, modern limb-salvage practice has a relatively low threshold for such minor amputations in the presence of deteriorating diabetic foot wounds. 28 This is reflected in recent nation-wide increases in the rate of diabetes-related minor amputations in the United States, manifested as a 50% increase in the total amputation rate in the years 2009–2015. 29…”
Section: Discussionmentioning
confidence: 99%
“…Surgical correction of significant deformity should be considered soon after DFU healing has occurred, and sometime, even to achieve healing. 79 Likewise, it will be important to ensure any revascularisation undertaken during the initial phase of DFU care is monitored and pharmacotherapy adjusted to ensure long-term durability. 80 , 81 The biomechanical considerations are perhaps the most vital, representing a dynamic process and are discussed further below.…”
Section: Risk Factors For Diabetic Foot Ulcerationmentioning
confidence: 99%
“…It emphasizes the importance of a multidisciplinary approach involving diabetology, podiatry, vascular surgery, orthopedics and other specialties, as well as a pathway to ensure timely footcare and urgent referral [ 108 ]. For example, transfer of care to dedicated clinics that specialize in strategies such as off-loading, debridement, managing infection and restoring arterial flow, in order to avoid amputation, are essential and provide optimal limb salvage treatment [ 66 , 87 ]. However, a recent national audit in the UK found that these services are currently fragmented and confusing, leaving patients in the community without the necessary treatment [ 88 ].…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…A multidisciplinary footcare team with surgical and infection expertise may provide optimal limb salvage treatment [ 87 ]…”
Section: Figurementioning
confidence: 99%